the effect of organizing the university environment on increasing its efficiency and directing economic resiurces - محمود, سعد خضير (Journal of Planner and Development, 2012)
Technical education in Iraq Composed of, a complex system of technical competence and scientific, technical and administrative, which extends to cover large areas of the country and constitute a vicious circle between economic development, social and cultural rights through middle-management on the one hand, and between academic knowledge and political decision-making, which aims to bring such development On the other hand, in the light of that education is the actual technical extension applied to create the idea of complementarily between them. In Iraq, have been distributed institutes and technical colleges to achieve those goals, in addition to realizing the idea of integration between them and community, and integration of technical colleges developed and technical institutes old (host) through the creation of an environment university is seeking to Investment human and material resources are of workshops and laboratories, clubs, libraries and facilities sports, parks and public spaces, which is serving the students their leisure time, especially as hours of education and training in technical education is supposed to extend to long hours are different from other academic institutions. The current study Focus to examine the university environment with a focus on the idea of complementarily between colleges developed and technical institutes and the investment of available resources, which constitute one of the pillars of the idea of the development of these colleges and their impact in reducing the waste of economic resources, and will be the geographical area elected are complex institutions and technical colleges in Zafaraniya, which includes (Institute of Technology and its relationship with Baghdad College of Technology - Baghdad). This research shows the fragmentation of the university environment and inconsistency at multiple levels of fragmentation events and student activities and devote the idea of separation, isolation and lack of interaction between students within the environment one, plus a lack of investment in human resources varied in that environment and resorting to self-sufficiency, thereby contributing to the lack of direct economic resources properly.